2021
DOI: 10.1364/oe.440062
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced dynamic alignment and nonlinear-like optical transmission in liquid suspensions of 2D atomically thin nanomaterials

Abstract: Nonlinear optical property of atomically thin materials suspended in liquid has attracted a lot of attention recently due to the rapid development of liquid exfoliation methods. Here we report laser-induced dynamic orientational alignment and nonlinear-like optical response of the suspensions as a result of their intrinsic anisotropic properties and thermal convection of solvents. Graphene and graphene oxide suspensions are used as examples, and the transition to ordered states from initial optically isotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, the authors of ref neglected the thermal effects even though they used CW and high repetition-rate sources to perform the experiments. Moreover, it has already been shown that thermal effects can also lead to the alignment of two-dimensional structures at the same time that it induces thermo-optical nonlinearities, reinforcing the importance of thoroughly analyzing the physical mechanisms responsible for the observed phenomenon to avoid mistaken inferences about the optical properties of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors of ref neglected the thermal effects even though they used CW and high repetition-rate sources to perform the experiments. Moreover, it has already been shown that thermal effects can also lead to the alignment of two-dimensional structures at the same time that it induces thermo-optical nonlinearities, reinforcing the importance of thoroughly analyzing the physical mechanisms responsible for the observed phenomenon to avoid mistaken inferences about the optical properties of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…When SSPM originates from the electronic or molecular orientation of nonlinear media, it relates to the real part of third-order electronic susceptibility ( ( ) 3 c ) [38]. However, as discussed in [39], relying on the relationship between ( ) 3 c and n 2 is often erroneous. The optical nonlinearity associated with thermal effects does not originate from electronic contributions, but does have an intensity dependence, which can be expressed as n n I, th th 2,…”
Section: Spatial Self-phase Modulationmentioning
confidence: 99%